A Novel High Power Factor and Soft Switching SAB-SWISS Rectifier With High-Low-High-Low Modulation and Hybrid Frequency Control - Bo Zeng; Ziwen Yang; Shi Yan; Lingjuan Tan; Shaojun Xie (IEEE Access)
A novel SWISS rectifier based on single active bridge converter (SAB-SR) is proposed. The high-low-high-low (HLHL) voltage waveform modulation to realize soft-switching for the power switches and the hybrid frequency control scheme to achieve high power factor are presented. The switching modes of the SAB-SR are examined detailly to illustrate the soft-switching operational process, and the calculation methods for the modulation duration are introduced. The hybrid boundary-conduction-mode (BCM) with variable frequency switching and discontinuous-conduction-mode (DCM) with constant frequency switching based on the primary current of the transformer are adopted to achieve low distortion input currents with limited switching frequency range. The operational characteristics of the rectifier under hybrid frequency control is analyzed. The simulation and experimental results validate that the SAB-SR with HLHL modulation and hybrid frequency control can achieve high power factor and soft-switching operation under wide power range.